KELALAIAN PELAKSANAAN PUTUSAN ATAS TINDAK PIDANA KORUPSI (PUTUSAN MAHKAMAH AGUNG NOMOR. 321. K/PID.SUS/2019) - Rizqi Maharani Ginting; Abdul Ficar Hadjar (Reformasi Hukum Trisakti, 2023)
Supreme Court Decision Number 321 K/PID.SUS/2019 discusses acts against the law related to criminal acts of corruption. The problem in this research is why the forced detention measures were not applied in the corruption trial process referred to in the Supreme Court Decision Number 321 K/PID.SUS/2019 and what are the legal consequences of the corruption criminal justice process which does not apply detention to the defendant in the case. The research method used is normative law. The results of the research and discussion concluded that the forced detention of the accused was not carried out due to wrong legal considerations. In addition, there are no legal consequences from the corruption trial process without detaining the accused, because the decision to detain is in the hands of law enforcement officials who consider that detention is not necessary for the accused. Conclusion in research